The Ensembl COVID-19 resource: ongoing integration of public SARS-CoV-2 data. Issue Volume 50:Issue D1(2022) (11th October 2021) - De Silva, Nishadi H; Bhai, Jyothish; Chakiachvili, Marc; Contreras-Moreira, Bruno; Cummins, Carla; Frankish, Adam; Gall, Astrid; Genez, Thiago; Howe, Kevin L; Hunt, Sarah E; Martin, Fergal J; Moore, Benjamin; et al.
Abstract: The COVID-19 pandemic has seen unprecedented use of SARS-CoV-2 genome sequencing for epidemiological tracking and identification of emerging variants. Understanding the potential impact of these variants on the infectivity of the virus and the efficacy of emerging therapeutics and vaccines has become a cornerstone of the fight against the disease. To support the maximal use of genomic information for SARS-CoV-2 research, we launched the Ensembl COVID-19 browser; the first virus to be encompassed within the Ensembl platform. This resource incorporates a new Ensembl gene set, multiple variant sets, and annotation from several relevant resources aligned to the reference SARS-CoV-2 assembly. Since the first release in May 2020, the content has been regularly updated using our new rapid release workflow, and tools such as the Ensembl Variant Effect Predictor have been integrated. The Ensembl COVID-19 browser is freely available at https://covid-19.ensembl.org .